2015
DOI: 10.1126/scitranslmed.aac7462
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic consensus anti–spike protein DNA vaccine induces protective immunity against Middle East respiratory syndrome coronavirus in nonhuman primates

Abstract: First identified in 2012, Middle East respiratory syndrome (MERS) is caused by an emerging human coronavirus, which is distinct from the severe acute respiratory syndrome coronavirus (SARS-CoV), and represents a novel member of the lineage C betacoronoviruses. Since its identification, MERS coronavirus (MERS-CoV) has been linked to more than 1372 infections manifesting with severe morbidity and, often, mortality (about 495 deaths) in the Arabian Peninsula, Europe, and, most recently, the United States. Human-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
312
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(318 citation statements)
references
References 55 publications
3
312
0
3
Order By: Relevance
“…Another encouraging study also reported a partial protection in NHPs using only DNA vaccine based on the consensus sequence of the S gene . This vaccine was delivered to Rhesus macaques in 3 homologous DNA vaccinations, with 3‐week intervals.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Another encouraging study also reported a partial protection in NHPs using only DNA vaccine based on the consensus sequence of the S gene . This vaccine was delivered to Rhesus macaques in 3 homologous DNA vaccinations, with 3‐week intervals.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 96%
“…Most importantly, this vaccine was the first to undergo camel immunization. Two of 3 vaccinated dromedary camels developed S‐specific antibodies (Table ) . Overall, this vaccine induced high titer nAb in mice, camels, and monkeys and has now advanced to human clinical trials (discussed in the next section).…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 97%
“…Most candidate vaccines are still being evaluated in animal models. They have generally targeted the spike protein of MERS-CoV and are recombinant virus, subunit, DNA, or virus-like vector vaccines ( 60 , 63 67 ). One live-attenuated MERS-CoV candidate vaccine is in early development ( 66 ).…”
Section: Vaccinesmentioning
confidence: 99%
“…Experimental MERS-CoV infection studies and vaccine studies of a small number of dromedaries have been conducted in large animal Biosafety Level 3 facilities in the United States and overseas ( 19 ). In addition, 3 doses of a DNA vaccine containing the MERS-CoV spike protein induced humoral immunity in dromedaries ( 60 ). In a recent study, a modified vaccinia virus Ankara vaccine that expresses the MERS-CoV spike protein was administered intranasally and intramuscularly to dromedaries; when challenged intranasally with MERS-CoV, vaccinated dromedaries had fewer signs of respiratory infection and lower MERS-CoV titers in the upper respiratory tract compared with unvaccinated dromedaries ( 76 ).…”
Section: Vaccinesmentioning
confidence: 99%
“…An optimized DNA vaccine encoding full-length S protein of MERS-CoV was able to elicit antigen-specific neutralizing antibodies in mice, camels and rhesus macaques (non-human primates, NHPs), with six of the eight vaccinated macaques showing no radiographic evidence of infiltration after MERS-CoV challenge. Interestingly, potent antigen-specific cellular immune responses were induced in the immunized macaques, suggesting that T cell responses may also play a role in MERS-CoV protection [25]. Inovio Pharmaceuticals Inc., in collaboration with GeneOne Life Science, will perform a Phase I clinical trial for this DNA-based vaccine [26].…”
Section: Current Status Of Mers Vaccinesmentioning
confidence: 99%